Literature Study of the Application of Skimming Techniques to Improve Speed ​​Reading Ability in Indonesian Language Lessons for Class V Elementary School Students: Studi Literatur Penerapan Teknik Skimming Dalam Meningkatkan Kemampuan Membaca Cepat Pada Pelajaran Bahasa Indonesia Siswa SD Kelas V - Dien Rufaida; Kemil Wachidah (Academia Open, 2022)
The purpose of this study is to describe the process of skimming techniques for elementary school students to improve reading skills. This study uses a literature study approach using the Systematic Literature Review (SLR) method. The subject is a journal that comes from Google Scholar with the research limitations of elementary school students who have been analyzed by researchers. Based on the results of Hawa's research that there is an increase in reading ability in Indonesian language lessons for students. This can be seen from the first and second cycles of active students, educators and student learning outcomes. In the first cycle, the total score for the results of the observation of student activity, the score obtained was 62.5% with a sufficient predicate. While in the second cycle the number of scores obtained on student learning activity got a score of 87.5% with a good and very good predicate. Students. According to Fitria's research, based on the results of the average speed reading ability by skimming on a sample of 16 students, which was adjusted with a five-scale percentage interval to determine the level of student ability. After adjusting for a five-scale score interval, it is known to have obtained a score of 95.25%, therefore this score is included in the Very Good category. It can be proven that students' ability to read quickly using skimming techniques is included in the very good category during the speed reading test and in understanding the content of reading the text. From the results of analyzing previous research conducted by Hawa, Muhtar, and Fitria that skimming technique can help students' speed reading ability in Indonesian language lessons.